Aditivos naturais na alimentação de poedeiras comercias - Cordeiro, Carla Nágila (2023)
In this research, three experiments were carried out with birds from the commercial Lohmann LSL-LITE line. The objective was to evaluate the effect of using natural additives, organic acids, essential oils and probiotics, ethanolic extract of acerola residue (EEAR) and Moringa Oleifera leaf hay (MOL) in the diets of light layers. In the first experiment, the addition of organic acids (benzoic acid), essential oils (thymol, eugenol and piperine) and probiotics (Bacillus licheniformis e Bacillus subtilis) to feed was evaluated. We used 288 laying hens with 36 weeks of age, distributed in a completely randomized design (CRD), with four treatments (control feed without additives; feed with a combination of organic acid and essential oils (0.0300%); feed with probiotics (0.0625%) and feed with organic acid and essential oils (0.0300%) + probiotics (0.0625%)) with nine replications of eight birds each. There was no significant effect of treatments on the variables of egg performance and quality, quantity of phenolic compounds, antioxidant capacity and activity, and lipid stability of egg yolk. It is concluded that the addition of organic acids, essential oils and probiotics, alone or in combination, to light layer rations does not influence performance, egg quality and lipid oxidation of egg yolks. In the second experiment, the inclusion of EEAR in layer rations was evaluated. 192 birds with 30 weeks of age were used, distributed in CRD, with four treatments (feed without added antioxidant; feed with addition of 200ppm of synthetic antioxidant - BHT; feed with 2000ppm of EEAR; feed with 3000ppm of EEAR) with six replications of eight birds each. There was no significant effect of treatments on performance variables and egg quality characteristics. Eggs from birds fed with diets containing EEAR and synthetic antioxidants showed greater antioxidant capacity and greater lipid stability in the yolks when compared to eggs resulting from birds fed with diets without added antioxidants. The use of EEAR in the feeding of light layers improves the antioxidant capacity and lipid stability of egg yolk, without influencing egg performance and quality. In the third experiment, the inclusion of MOL as an additive in the feed of light layers was evaluated. 192 birds with 45 weeks of age were used, distributed in CRD, in four treatments (ration with 0; 0.75%; 1.25% and 1.75% of MOL), with six replications of eight birds each. There was no significant effect of treatments on performance variables and egg quality characteristics, except for yolk color, which intensified with increasing MOL inclusion levels. MOL inclusion levels positively influenced the antioxidant capacity and activity of the yolk and the TBARS of the yolk, liver and uterus. Levels of 1.25% and 1.75% of MOL provided a higher concentration of phenolic compounds in the yolk and lower TBARS values in the ovary. The addition of up to 1.75% MOL to the feed of light commercial layers was efficient in improving yolk color, increasing the concentration of phenolic compounds and reducing lipid peroxidation in the yolk and organs (liver, ovary and uterus).